2021
DOI: 10.3390/antibiotics10020155
|View full text |Cite
|
Sign up to set email alerts
|

Third Generation Cephalosporin Resistant Enterobacterales Infections in Hospitalized Horses and Donkeys: A Case–Case–Control Analysis

Abstract: In human medicine, infections caused by third-generation cephalosporin-resistant Enterobacterales (3GCRE) are associated with detrimental outcomes. In veterinary medicine, controlled epidemiological analyses are lacking. A matched case–case–control investigation (1:1:1 ratio) was conducted in a large veterinary hospital (2017–2019). In total, 29 infected horses and donkeys were matched to 29 animals with third-generation cephalosporin-susceptible Enterobacterales (3GCSE) infections, and 29 uninfected controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…Multidrug resistance indicated by resistance to three or more different antimicrobial classes [ 32 ] was noted for all ESBL-E isolates that caused a clinical infection in our study population. The resistance to different antimicrobials was also very similar to the antibiograms published in the study by Shnaiderman-Torban [ 33 ]. The only remarkable difference was the susceptibility to amikacin; in our study 92% of the strains were susceptible to amikacin, whereas only 76% of the ESBL-E were susceptible to amikacin in the Shnaiderman-Torban study [ 33 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Multidrug resistance indicated by resistance to three or more different antimicrobial classes [ 32 ] was noted for all ESBL-E isolates that caused a clinical infection in our study population. The resistance to different antimicrobials was also very similar to the antibiograms published in the study by Shnaiderman-Torban [ 33 ]. The only remarkable difference was the susceptibility to amikacin; in our study 92% of the strains were susceptible to amikacin, whereas only 76% of the ESBL-E were susceptible to amikacin in the Shnaiderman-Torban study [ 33 ].…”
Section: Discussionsupporting
confidence: 80%
“…The resistance to different antimicrobials was also very similar to the antibiograms published in the study by Shnaiderman-Torban [ 33 ]. The only remarkable difference was the susceptibility to amikacin; in our study 92% of the strains were susceptible to amikacin, whereas only 76% of the ESBL-E were susceptible to amikacin in the Shnaiderman-Torban study [ 33 ]. This might reflect the habits of antimicrobial usage as horses in Finland extremely seldom receive amikacin due to financial restraints whereas in Israel most foals admitted to the hospital receive ampicillin and amikacin for broad-spectrum antimicrobial coverage [ 34 ].…”
Section: Discussionsupporting
confidence: 80%
“…Fluoroquinolones, as well as third-generation cephalosporins, are considered by World Health Organization (WHO) as critically important antimicrobials in human medicine, classified with the priority criterion 1 [ 43 ]. Consequently, the growing percentage of resistance against these antibiotics represent a serious concern of public health with important implication for clinical practice both in human and veterinary medicine [ 44 , 45 ]. Traditionally sulfonamides are considered to have good antimicrobial activity against S. zooepidemicus , with low resistance rates as stated by Feary et al [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Israeli case control study on 3GC-resistant Enterobacterales infections in hospitalized horses and donkeys showed that the Klebsiella spp. were the most common 3GC-resistant Enterobacterales detected ( Shnaiderman-Torban et al, 2021 ). However, it remains difficult to detect high-risk clonal lineages of K. pneumoniae through epidemiological and genomic analyses in horses (e.g., Trigo da Roza et al, 2019 ; Loncaric et al, 2020 ; Shnaiderman-Torban et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%